Export Performance and Trade Facilitation Reform Hard and Soft Infrastructure - Wilson, John S. (The World Bank, 2010)
The authors estimate the impact of aggregate indicators of "soft" and "hard" infrastructure on the export performance of developing countries. They build four new indicators for 101 countries over the period 2004-07. Estimates show that trade facilitation reforms do improve the export performance of developing countries. This is particularly true with investment in physical infrastructure and regulatory reform to improve the business environment. Moreover, the findings provide evidence that the marginal effect of infrastructure improvement on exports appears to be decreasing in per capita income. In contrast, the impact of information and communications technology on exports appears increasingly important for richer countries. Drawing on estimates, the authors compute illustrative exports growth for developing countries and ad-valorem equivalents of improving each indicator halfway to the level of the top performer in the region. As an example, improving the quality of physical infrastructure so that Egypt's indicator increases half-way to the level of Tunisia would increase exports by 10.8 percent. This is equivalent to a 7.4 percent cut in tariffs faced by Egyptian exporters across importing markets